Small-Size Seven-Band WWAN/LTE Antenna with Distributed LC Resonant Circuit for Smartphone Application - Yan-Wu Liang; Hao-Miao Zhou (International Journal of Antennas and Propagation)
A compact small-size coupled-fed antenna composed of an inverted L-shaped feeding strip and a shorting strip with double branches for the WWAN/LTE bands operation in the internal smartphone application is presented. With the help of a novel distributed LC resonant circuit, the proposed antenna can not only realize the miniaturization (15 × 28 × 4 mm3) and multiband to cover 2G/3G/4G bands but also be tuned and optimized easily. The measured bandwidth with 3 : 1 VSWR is 163 MHz (804–967 MHz) at the low-band and 1615 MHz (1665–3280 MHz) at the high-band. What is more, the lowest measured efficiency in the whole frequency band is more than 52% for practical applications. The operating principles and main parameters are detailed below. And successful simulation, fabrication, and measurement of the proposed antenna are shown in this paper.